Existence of Consumer Protection in the Katsuwonus Pelamis Process as a Safe Culinary - Telly Sumbu; Donald Albert Rumokoy; Wulanmas Anna Patricya Gracya Frederik (Susbtantive Justice International Journal of Law, 2023)
Katsuwonus Pelamis is a fishery commodity originating from the waters of the bay in Indonesia, Cakalang Fufu is a popular culinary dish with processed fish that is processed quickly, served fresh, frozen, canned or dried, which has become the object of fishing for fishermen because it is considered profitable. The reality of management that does not have adequate quality control, while the paradigm of entrance market is skipjack tuna management as soon as possible has been carefully tested for safety aspects before the product is released to the market. This action is a legal event that causes harm to consumers who are accommodated by legal protection. This study aims to describe the process of catching, storing and marketing skipjack tuna as a safe food product from the perspective of consumer law protection, and to describe the forms of law enforcement against the circulation of unsafe food products. This research uses the type of research socio legal research. The description of the research results shows that the process of catching, storing and marketing skipjack tuna specifically in North Sulawesi still uses traditional methods, but the urgency and safety aspects of catching results cannot be guaranteed, including the process of storing and marketing skipjack tuna does not comply with the provisions. Standard procedures are ignored so that the impact of the expected information is given to consumers from the capture process to the final consumer.